Synthesis of cobalt- ferrite and zinc oxide metal nanoparticles based-bentonite using SDS and their investigation as catalysts in synthesis of benzylbarbiturocoumarins - Baminejhad, Pegah; Sheikhhosseini, Enayatollah; Yahyazadehfar, Mahdieh (Frontiers in Chemistry, 2024)
In this research, a suitable and efficient CoFe2O4@ZnO@Bentonite nano-catalyst was designed and synthesized by using zinc oxide (ZnO) and cobalt ferrite (CoFe2O4) nanoparticles and bentonite by microwave irradiation. Characteristics of the synthesized nanocomposite were investigated by Fourier transform infrared (FT-IR), scanning electron microscope (SEM), energy dispersive X-ray (EDX), transmission electron microscope (TEM), X-ray diffraction (XRD), Bruner- Emmett-Teller (BET) and vibrating sample magnetometer (VSM) techniques. The produced catalyst was effectively employed as a supported solid acid catalyst in mildly agitated three-component reactions involving aromatic aldehydes, 4-hydroxycoumarin, and 1,3-dimethyl-barbituric acid in a single pot to produce benzylbarbiturocoumarins. Starting materials were condensed via three C–C bond formation by CoFe2O4@ZnO@Bentonite as an efficient, recyclable, and environmentally safe nanocatalyst to obtain target products. The advantages of this method include using a natural substrate, small amounts of catalyst, aqueous media, performing reactions at ambient temperature, simple separation and purification of products, and good yields with short reaction times.